Tribal Commissions and Committees in India. - Bhanage, N.P. (Bombay, 1993)
Tribal Commissions have a different perspective as compared to the other enquiry commissions which are appointed to investigate into the events of particular importance like police firing or occurrence of the natural catastrophe or investigate into the alleged charges against persons or institutions. The procedure followed by such latter type of enquiry commissions is in the nature of judicial enquiry. On the other hand, the reports of the Tribal Commissions are more or less in the form of recommendations and therefore there is a marked difference in the basic approach and the working pattern of the two types of commissions. Apart from the Commissions appointed under Article 280(1), 349, 340 of the Constitution of India, the Ministries of the Planning Commission also appoints the Working Groups or Study Groups comprising eminent personalities in the requisite field and their reports are taken into consideration at various levels at the time of preparation of Plan Documents.
Keywords: Commissions and Committees India 1947 1992